The Influence of Learning Cycle Model Against the Motivation of Learning and Critical Thinking Skills of Students - Hidayah, Farida; Alimah, Siti; Anggraito, Yustinus Ulung (Journal of Biology Education, 2019)
This research aims to know the influence of motivation towards Learning Cycle of learning and critical thinking skills of students on the material of the human digestive system in SMP Negeri 03 Jekulo. The sample used is grade VIII VIII C and D taken with the technique of convenience sampling and research design a non-randomized control group pretest-posttes design. Data obtained in the form of motivation and critical thinking skills as well as the response of teachers and students towards learning Learning Cycle model. Data analysis using SPSS 16.0. The research results obtained studying motivations of students after learning Learning Cycle has increased from 76.87 with higher category be the category with very tinngi 84.67. Results the average critical thinking skills has increased from 76.34 with critical categories into classes with 82.11 wants a category of highly critical. The t-test based on posttest showed thitung > 11.628 from ttabel 2.073 which means there is a significant difference. The response of the students towards the Learning Cycle shows interest because of the interesting activities and serves the appropriate issues with everyday life. The teacher gave a positive response, namely students became active in learning, so that students acquire the knowledge of the concept of direct experience of the menjadiikan pengetahuaanya longer remember.  The conclusions of this research are the Learning Cycle model provides a positive influence motivation towards learning and critical thinking skills on the material of the human digestive system in SMP Negeri 3 jekulo.